2004
DOI: 10.1081/ese-200034072
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Nonionic Surfactants with Immobilized TiO2 in an Airlift Reactor

Abstract: The photocatalytic degradation of a nonionic surfactant, Sanonic SS-90 (polyoxyethylene alkyl ether) which is one of polyoxyethylene nonionic surfactants, in water has been investigated using immobilized titanium dioxide (TiO2) photocatalyst. An external UV irradiation type airlift reactor was used as a photoreactor. The effects of initial nonionic surfactant concentration, intensity of UV light, and concentrations of TiO2 photocatalyst on degradation rate of Sanonic SS-90 were examined. The photocatalytic dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The degradation rate constant, k r , represents the overall or apparent degradation rate constant because it may depend on the UV light intensity and photocatalyst loading in the photocatalytic reactor. In fact, as well as our previous studies, , k r was found to be proportional to I 0.5 or S L 0.5 . Results similar to those observed here were also reported elsewhere. , …”
Section: Modelingsupporting
confidence: 89%
See 1 more Smart Citation
“…The degradation rate constant, k r , represents the overall or apparent degradation rate constant because it may depend on the UV light intensity and photocatalyst loading in the photocatalytic reactor. In fact, as well as our previous studies, , k r was found to be proportional to I 0.5 or S L 0.5 . Results similar to those observed here were also reported elsewhere. , …”
Section: Modelingsupporting
confidence: 89%
“…Increased catalyst loading improved the number of active sites in the slurry reactor. It should be noted, however, that this may be confounded at higher loading due to light scattering and shielding. , On the basis of the findings described above, the reaction rate constant k r in the region where the degradation rate constant is proportional to the mean TiO 2 particle concentration in the reactor, C P , was assumed to be given as follows: Although this relationship is similar to that presented in our previous studies, , the term for particle diameter is included in this equation to consider the different catalyst diameters. It can be seen from Figure b, in fact, that the apparent reaction rate constant increased with decreasing photocatalyst diameter.…”
Section: Modelingmentioning
confidence: 99%
“…The most widely applied semiconducting material for photocatalytic purposes is titanium dioxide (TiO 2 ). TiO 2 -based photocatalysis was combined with sonolysis, providing an efficient technique for mineralization of organic pollutants . TiO 2 -mediated photodegradation was also used for decomposition of various amino acids, as well as for surfactant decontamination. …”
Section: Introductionmentioning
confidence: 99%
“…33 TiO 2 -mediated photodegradation was also used for decomposition of various amino acids, [34][35][36] as well as for surfactant decontamination. [37][38][39][40][41][42][43] The objective of this study is to investigate the TiO 2 -based photocatalytic treatment of 1,5-naphthalenedisulfonate (NDS) in a laboratory-scale reactor in order to contribute to the elucidation of the oxidative degradation mechanism of this surfactant. The changes during the photocatalysis were followed by measuring the pH, the absorption and emission spectra, the sulfate concentration, and the total organic carbon (TOC) content of the mixture irradiated.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently when photocatalytic particles are immobilized in thin films instead of being used in water environment, the activation environment is to be regulated cautiously due to the inherent reduction of photocatalytic area [67] and the emerging recombination problem [68,69]. Photo-induced carriers are transmitted at the boundary of the photocatalyst and the adsorbed material and reaction efficiency is reduced for solid films because of reduced effective catalyst surface [57,70].…”
Section: Increasing the Performance Of Catalytic Thin Filmsmentioning
confidence: 99%